A Pair of Spectacles. (2nd July 2020) - Jones, Susan H.
ABSTRACT: This study offers an example of 'standing theology', as distinguished from sitting theology and kneeling theology. The occasion was Passion Sunday 2020 when at the request of the Archbishops of Canterbury and York all churches were locked up. The Gospel reading and the address were read by the Dean standing outside the cathedral on a windswept day.